Legal Aspects of Hotel Policy towards Employees Due to the Covid 19 Pandemic in Parapat - Imman Yusuf Sitinjak; Rosita Nainggolan (Budapest International Research and Critics University, 2021)
This study aims to determine how the hotel policies in laying off employees are reviewed according to the labor law in Law No. 13 of 2003 and Civil Law in terms of work agreements. The interest of having a job is the most important interest of every society. Because by having a job, people have income to meet their daily needs.This study discusses the policy of the hotel to lay off employees while in the work agreement, employees have the right to pay that they must receive in accordance with the work contract. It is true that no one knows if the COVID 19 pandemic that attacks all countries in the world has had many adverse effects on society. One of the most important impacts is the decline in income and business due to government policies that require reducing the number of people gathering or creating crowds in Indonesia. As a result of this decreased income, employers made efforts to lay off employees to prevent their business from rolling down. However, this policy creates losses for employees who work in the place of business. The conclusion that can be drawn is a violation of the contents of the agreement if when laying off employees or workers but they do not give their rights, namely salary, because salary is the right of every employee who works, and when leaving but not returning to employ an employee where the contract is still valid it is a violation of the contents of the contract, except with the agreement and conditions to terminate the employee's unilateral contract with compensation for severance pay by the hotel. However, this will be difficult if the employees who are dismissed and not given a salary and who are not called back to work are employees who work under an oral agreement. Because there is no written agreement that is binding and proves what was agreed upon orally between the employee and the entrepreneur.